Child Poverty and Deprivation in Uganda - Adebayo, Sanni T. (Journal of Madras School of Socila Work, 2019)
The need and purpose of this paper is to examine Child Poverty and Deprivation in Uganda. Child poverty has been a concern of Majority of Researchers and Stake holders around the World, especially in Uganda. In Uganda, the situation analysis currently is nothing to write home about. There are challenges associated with Child Poverty and Deprivation such as basic health care; adequate nutrition, water and sanitation; nurturing and stimulation within caring, safe and clean Environment.